Precisely timed signal transmission in neocortical networks with reliable intermediate-range projections - Nawrot, Martin P.; Schnepel, Philipp; Aertsen, Ad; Boucsein, Clemens (Frontiers in Neural Circuits, 2009)
The mammalian neocortex has a remarkable ability to precisely reproduce behavioral sequences or to reliably retrieve stored information. In contrast, spiking activity in behaving animals shows a considerable trial-to-trial variability and temporal irregularity. The signal propagation and processing underlying these conflicting observations is based on fundamental neurophysiological processes like synaptic transmission, signal integration within single cells, and spike formation. Each of these steps in the neuronal signaling chain has been studied separately to a great extend, but it has been difficult to judge how they interact and sum up in active sub-networks of neocortical cells. In the present study, we experimentally assessed the precision and reliability of small neocortical networks consisting of trans-columnar, intermediate-range projections (200 – 1000 µm) on a millisecond time-scale. Employing photo-uncaging of glutamate in acute slices, we activated a number of distant pre-synaptic cells in a spatiotemporally precisely controlled manner, while monitoring the resulting membrane potential fluctuations of a post-synaptic cell. We found that signal integration in this part of the network is highly reliable and temporally precise. As numerical simulations showed, the residual membrane potential variability can be attributed to amplitude variability in synaptic transmission and may significantly contribute to trial-to-trial output variability of a rate signal. However, it does not impair the temporal accuracy of signal integration. We conclude that signals from intermediate-range projections onto neocortical neurons are propagated and integrated in a highly reliable and precise manner, and may serve as a substrate for temporally precise signal transmission in neocortical networks.